262 Tumoral DKK1 expression correlates with better clinical outcomes in patients with advanced esophagogastric cancer (EGC) treated with DKN-01. (9th November 2020) - Klempner, Samuel; Kagey, Michael; Sirard, Cynthia; Sirard, Cynthia
Abstract : Background: Dickkopf-1 (DKK1) modulates Wnt signaling and contributes to an immune suppressive tumor microenvironment. DKN-01 (D), a neutralizing DKK1 antibody, has demonstrated safety and clinical activity in advanced EGC either as a monotherapy or in combination with paclitaxel (pac) or pembrolizumab (pem). We report response and survival outcomes in EGC patients (pts) by high/low tumoral DKK1 expression treated with D. Methods: We enrolled advanced EGC pts in a Phase 1b/2a study of D as monotherapy or in combination with pac or pem. Tumoral DKK1 mRNA expression was assessed by an in situ hybridization RNAscope assay. Objective response rate (ORR), disease control rate (DCR), progression free survival (PFS) and overall survival (OS) were compared between DKK1 high and low groups. Kaplan-Meier method and Cox-PH model were used for survival analysis and logistic regression was used for clinical benefit/response outcome. Results: 69 EGC pts were enrolled to receive D alone or in combination with pac or pem and had tumoral DKK1 expression available. 60 pts (87%) were male, median age 65 (range 28, 81). 59 pts had adenocarcinoma [19 esophageal (28%), 40 GEJ/gastric (58%)] and 10 pts with ESCC. 65% had ≥2 prior therapies (range 1, 5). 23 pts with DKK1 high (H-score ≥ upper-tertile [≥39]) had an ORR of 22% (5 PR/23), DCR of 57% (13/23) while DKK1 low (H-score <39) had an ORR of 2% (1/46) and DCR of 26% (12/46). Median PFS was 12.1 weeks in DKK1 high vs. 6.0 weeks in DKK1 low; HR of 0.58 (95%CI: 0.34, 1.0). Median OS was 31.6 weeks in DKK1 high vs. 18 weeks in DKK1 low; HR of 0.70 (95%CI: 0.38, 1.3). Subgroup of pts (n=9) with immune checkpoint inhibitor (ICI) refractory disease treated with D + pem demonstrated longer PFS and OS for DKK1 high pts (H-score ≥39, n=4) vs DKK1 low (n=5): PFS 12.8 weeks vs 6.0 weeks; HR of 0.16 (95%CI: 0.02, 1.5) and OS 46 weeks vs. 16 weeks, respectively; HR of 0.22 (95%CI: 0.03, 2.0). Conclusions: High levels of tumoral DKK1 expression correlate with improved clinical outcomes in heterogeneous EGC pts treated with D monotherapy or in combination. Previously we have demonstrated greatest clinical benefit in ICI-naïve, DKK1 high G/GEJ adenocarcinoma treated with D + pem. 1 DKK1-high ICI refractory pts treated with D + pem experienced longer PFS and OS compared with pts with low DKK1 expression. DKK1 as a predictive biomarker for DKN-01 is being evaluated in ongoing studies. Trial Registration: NCT02013154 Ethics Approval: WIRB (Western Institutional Review Board) Institution's Ethics Board, approval number 20140759 Reference: Klempner S, Bendell J, Villaflor V, Tenner L, Stein S, Naik G, Sirard C, Kagey M, Chaney M, Strickler J. DKN-01 in combination with pembrolizumab in patients with advanced gastroesophageal adenocarcinoma (GEA): tumoral DKK1 expression as a predictor of response and survival. J Clin Oncol 2020;38(suppl 4; abstr 357).